Right-left digit ratio (2D:4D) and maximal oxygen uptake - Hill, R.; Spson, B.; Manning, J.; Kilduff, L. (Journal of Sports Sciences, 2012)
A low digit ratio (2D:4D) and low 2D:4D in the right compared with the left hand (right-left 2D:4D) are thought to be determined by high in utero concentrations of testosterone, and are related to "masculine" traits such as aggression and performance in sports like running and rugby. Low right-left 2D:4D is also related to sensitivity to testosterone as measured by the number of cytosine-adenine-guanine triplet repeats in exon 1 of the androgen receptor gene. Here we show that low right-left 2D:4D is associated with high maximal oxygen uptake ([Vdot]O2max), high velocity at VO2max, and high maximum lactate concentration in a sample of teenage boys. We suggest that low right-left 2D:4D is linked to performance in some sports because it is a proxy of high sensitivity to prenatal and maybe also circulating testosterone and high VO2max.